2020
DOI: 10.1101/2020.04.02.021758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gain of channel function and modified gating properties in TRPM3 mutants causing intellectual disability and epilepsy

Abstract: 33Developmental and epileptic encephalopathies (DEE) are a heterogeneous group of disorders 34 characterized by epilepsy with comorbid intellectual disability. Recently, two de novo 35 heterozygous mutations in the gene encoding TRPM3, a calcium permeable ion channel, were 36 identified as the cause of DEE in eight probands, but the functional consequences of the 37 mutations remained elusive. Here we demonstrate that both mutations (V990M and P1090Q) 38 have distinct effects on TRPM3 gating, includin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The integration of cycles of computational and experimental analysis enabled us to provide mechanistic molecular insights into the different mechanisms by which two proximal candidate KCNC2 VUSs lead to DEE-like phenotypes. DEE has been previously linked to dysfunction of other ion channels 58,59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of cycles of computational and experimental analysis enabled us to provide mechanistic molecular insights into the different mechanisms by which two proximal candidate KCNC2 VUSs lead to DEE-like phenotypes. DEE has been previously linked to dysfunction of other ion channels 58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…The integration of cycles of computational and experimental analysis enabled us to provide mechanistic molecular insights into the different mechanisms by which two proximal candidate KCNC2 VUSs lead to DEE-like phenotypes. DEE has been previously linked to dysfunction of other ion channels 58,59 . Moreover, Kv3 channel family members have been previously associated with neurological disorders such as ataxias, epilepsies, schizophrenia, and Alzheimer’s disease 60 .…”
Section: Discussionmentioning
confidence: 99%
“…TRPM3 is expressed in the brain, and its overactive mutations cause intellectual disability and epilepsy in humans (Dyment et al, 2019;Van Hoeymissen et al, 2020;Zhao et al, 2020). Primidone crosses the blood-brain barrier (Nagaki et al, 1999), while specific data for isosakuranetin are not available, several very similar flavonoid molecules, such as liquiritigenin and naringenin (also TRPM3 inhibitors) have been shown to cross the blood-brain barrier (Youdim et al, 2003;Li et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…This nomenclature has been used by others (de Sainte Agathe et al, 2020; Gauthier et al, 2021) including Human Gene Mutation Database (Stenson et al, 2017) and OMIM (https://www.omim.org/). Others have reported this same variant as NM_001007471.2:c.2986G>A, NP_001007472.2:p.(Val990Met) (Van Hoeymissen et al, 2020; Zhao et al, 2020). In ClinVar (https://www.ncbi.nlm.nih.gov/clinvar/) the nomenclature used for this variant is NM_001366145.2:c.3004G>A; NP_001353074.1:p.(Val1002Met).…”
Section: Methodsmentioning
confidence: 95%
“…Subsequently, other individuals with a similar phenotype, though lacking epilepsy, were reported with the same recurrent variant (de Sainte Agathe et al, 2020; Gauthier et al, 2021). Although initial reports did not include any functional studies, subsequent in vitro experiments in heterologous expression systems demonstrated pathogenic gain‐of‐function through altered gating and conductance (Held et al, 2018; Van Hoeymissen et al, 2020; Zhao et al, 2020). The channels expressing the recurrent substitution exhibit increased basal activity, enhanced sensitivity to the TRPM3 agonist pregnenolone sulfate, increased thermal sensitivity, and increased permeability via a non‐canonical or “alternative” conductance pathway previously identified in TRPM3 (Van Hoeymissen et al, 2020; Vriens et al, 2014; Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%